(3GdaQhSjI HQSe GdLgGO heG CYO Gddg ddeLGgOjf ef GdYHGOs
(3ChdgG (B:s
(3bGd Gddg JHGQc hJYGdi ai Mb GdeLGgOjf ai SHjd Gddg (B( (3hdG JMSHf GdPjf bJdhG ai SHjd Gddg CehGJkG s
(3BNQgG (B:s
(3VQH GdOGjQ HGdhba, VQH GdOGjQ HGdOGNd,VQH GdefSH s
(3fSNI NRGFfjIs
(3QJHg Ydi (B52 (3HGHkG ai GfhGY GdMQhH YfGhjf GdGHhGH HGdKdKs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3HQhcdeGf (B- (3GdLRA (B1 - (3U (B905 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B4 - (3bSe eYGQa YGeg (B- (3U (B24 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdafhf GdMQHjI h GdaQhSjIs